2008
DOI: 10.1007/s11095-008-9772-3
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Makes Sense in Engineered Regenerative Medicine

Abstract: The use of antisense strategies such as ribozymes, oligodeoxynucleotides (ODNs) and small interfering RNA (siRNA) in gene therapy, in conjunction with the use of stem cells and tissue engineering, has opened up possibilities in curing degenerative diseases and injuries to non-regenerating organs and tissues. With their unique ability to down-regulate or silence gene expression, antisense oligonucleotides are uniquely suited in turning down the production of pathogenic or undesirable proteins and cytokines. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 114 publications
(94 reference statements)
0
28
0
1
Order By: Relevance
“…[23][24][25][26][27][28] We have performed an in vitro and in vivo study to ascertain the effects of an antisense anti-prion treatment on the inhibition of growth and on the induction of glioma cell death. Many different preclinical and clinical studies have indicated a role for antisense nucleotides as therapeutics for malignant diseases 18 and, in particular for astrocytomas. [29][30][31] In this study, three antisense molecules against PRNP were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] We have performed an in vitro and in vivo study to ascertain the effects of an antisense anti-prion treatment on the inhibition of growth and on the induction of glioma cell death. Many different preclinical and clinical studies have indicated a role for antisense nucleotides as therapeutics for malignant diseases 18 and, in particular for astrocytomas. [29][30][31] In this study, three antisense molecules against PRNP were used.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular-based strategies involving ODNs, siRNAs, microRNAs and protein peptides have been recently proposed. 18 Among these, ODNs, consisting of 18-25 nucleotides long DNA sequences complementary to a target RNA, were largely investigated as potential cancer therapeutic molecules. Once delivered into the cells, ODNs bind to their RNA counterparts and suppress expression of specific proteins.…”
Section: Prpmentioning
confidence: 99%
“…Tissue engineering deals with the reconstruction of degenerative tissues using three-dimensional cell-laden scaffolds, where morphogenesis is precisely induced and cell-matrix interaction is highly emphasized [41,42]. Gradual release of naked or formulated (i.e.…”
Section: Macroscopic Matrix Systemsmentioning
confidence: 99%
“…Therefore, it is imperative to suppress the expression of Col I in the application of SMSCs for chondrogenesis. RNA interference (RNAi) has provided a solution to meet this end (11,12). With either exogenous small interfering RNA (siRNA) or endogenously expressed shRNA that targets mRNA of Col I, the expression of Col I could be inhibited.…”
Section: Introductionmentioning
confidence: 99%